(untitled) (The Research of Medical Science Review, 2024)
Background: Non-adherence to tuberculosis (TB) treatment remains a critical public health challenge, impacting treatment success rates and facilitating the disease's spread. Pakistan ranks fifth among the 22 countries with the highest TB burden.Objective: To identify factors associated with non-adherence to TB treatment among patients with pulmonary tuberculosis.Method: This descriptive cross-sectional study was conducted at a tertiary care facility, Services Hospital Lahore. Data were collected from TB patients using a structured questionnaire, and analysis was performed in SPSS with chi-square tests applied (significance set at p < 0.05).Results: The study showed that 56% of participants were female, with 52% aged 18 to 25 years. Among them, 61% were married, 61% lived in urban areas, and 44% were illiterate. Around 26% of female participants were housewives. The study identified a positive association between age and non-adherence to medication, while illiteracy and low-income status showed a negative association with non-adherence (p < 0.05).Conclusion: Addressing socio-economic factors related to non-adherence to TB treatment is essential to improve treatment outcomes and decrease TB’s impact. By tailoring support based on patients' age, literacy, and income, healthcare providers can enhance adherence and contribute to more effective TB management strategies.